ANALISIS PENERAPAN SMART LIVING DALAM PEMBANGUNAN SMART CITY DI KOTA TEGAL - Arrohman, Zidni Dlia; Andriani, Wresti; Gunawan, Gunawan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Smart City is a city that can monitor and combine the situation of all infrastructure, both physical, social and business fields. The purpose of making a Smart City design is to make the city more efficient, prolonged, balanced and appropriate to live in. This design can also be applied to programming the rules of space, area or city, not only to the handling of cases in large cities. Each programming that uses the Smart City design intends to make the city sustainable. Regarding this is synergy with the programming of the landscape of prolonged natural tourism in Tegal City. The programming of the landscape to be raised is the realization of integrity and production power as well as the base of natural energy and multifunctional creation. To create programming purposes, Smart City designs that advance the use of IT can be applied to landscape programming zones and activities to be raised. IT systems used include intelligent inspection equipment installed in landscapes, features or equipment that can associate one network with another, computerization, social tools and GIS. The markers of success are measured by smart city design applications, including better management and organization, more advanced technology, the creation of good government, stakeholders understand and can use the technology applied, the economy increases, infrastructure development is better and the presence of areas is prolonged.